If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1(2 + -1x) = 22 5x + (2 * -1 + -1x * -1) = 22 5x + (-2 + 1x) = 22 Reorder the terms: -2 + 5x + 1x = 22 Combine like terms: 5x + 1x = 6x -2 + 6x = 22 Solving -2 + 6x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 6x = 22 + 2 Combine like terms: -2 + 2 = 0 0 + 6x = 22 + 2 6x = 22 + 2 Combine like terms: 22 + 2 = 24 6x = 24 Divide each side by '6'. x = 4 Simplifying x = 4
| 150m-75m+48000=50000-175m | | 3(n+.333)=2 | | 200m-125m+47750=50500+175m | | 3x^2+23x-6.5=0 | | 3x+6=2x+34 | | 3+6x=11+8x | | 2x+44=3y-9 | | 45=3(2x+7) | | m+2m+7m=60-5m | | 3+5x=10+3x | | 10v+23=93 | | 2x^2+64x+512=0 | | 7(d-5)+6= | | 2x^2+512=0 | | 3x-y(x+10)=9 | | z^2+2(1-i)z+2i=0 | | =1+3x | | x-6.1=5.3 | | 3x^5-14x^3-5x=0 | | -5k+2.7+2.4k+2.1k-5= | | 7x+4=19+2x | | h=24 | | 4x-(5x+5)=5x-47 | | y+1=-y+3 | | 3+5x=8+2x | | (x-y)*(4x-2y)= | | f(-x)=x^2-8x+9 | | 8x/3-3=29 | | (12x+3)+(-7x+5)= | | -2y-2.4+1.1-0.8y+2= | | w=-8/-7 | | -3(2n-3)=-4n+45 |